Insights on Microsatellite Characteristics, Evolution, and Function From the Social Amoeba Dictyostelium discoideum - Williams, Felicia N.; Scaglione, K. Matthew (Frontiers in Neuroscience, 2022)
Microsatellites are repetitive sequences commonly found in the genomes of higher organisms. These repetitive sequences are prone to expansion or contraction, and when microsatellite expansion occurs in the regulatory or coding regions of genes this can result in a number of diseases including many neurodegenerative diseases. Unlike in humans and other organisms, the social amoeba Dictyostelium discoideum contains an unusually high number of microsatellites. Intriguingly, many of these microsatellites fall within the coding region of genes resulting in nearly 10,000 homopolymeric repeat proteins within the Dictyostelium proteome. Surprisingly, among the most common of these repeats are polyglutamine repeats, a type of repeat that causes a class of nine neurodegenerative diseases in humans. In this minireview, we will discuss what is currently known about homopolymeric repeats and microsatellites in Dictyostelium discoideum and discuss the potential utility of Dictyostelium for identifying novel mechanisms that utilize and regulating regions of repetitive DNA.